Looking for Leroy [large type] - Carlson, Melody (Thorndike Press large print Christian fiction series., 2022)
"It's official: Brynna Phillips is done with men. They only break your heart. But just when she makes this declaration, her friend Jan convinces Brynna to join her on a camping vacation in Sonoma Wine Country. As they wind their way toward their destination, spanking-new mini camper in tow, Brynna recalls her teenage camp romance with a boy named Leroy. How can it have been nearly 30 years ago? All she remembers is that Leroy was a genuinely good guy and that his family owned a vineyard--in Sonoma. She doesn't even remember his last name. Jan insists they look for him, and the search begins.Beyond the slim chance they'd ever be able to find him are questions that have haunted Brynna for decades, including What is the point of digging up the past? and Can Leroy ever forgive me for losing touch? Bestselling author Melody Carlson invites you on a trip to rediscover the carefree days of youth and, just maybe, to get a second chance at love"--